Impact of the self-directed learning approach and attitude on online learning ineffectiveness: The mediating roles of internet cognitive fatigue and flow state - Shao, Mingming; Hong, Jon-Chao; Zhao, Li (Frontiers in Public Health, 2022)
Online learning has become an important learning approach in universities. However, since many students may have been exposed to online learning for the first time during this period of the COVID-19 pandemic, the quality factors of online learning and psychological distress of students need to be considered in the research on their learning. This paper discusses factors that influence the learning effect of university students in the online learning environment. A total of 377 university students participated in the survey. Structural equation modeling was used to verify the research hypotheses. The results show that the self-directed learning (SDL) approach and attitude can negatively predict students’ Internet cognitive fatigue (ICF) and positively predict their Flow, whereas perceived learning ineffectiveness can be predicted by Internet cognitive fatigue positively and by Flow state negatively. The results can be a reference for online teachers to enhance students’ online SDL attitude, and to discipline their SDL approach so as to promote online learning effectiveness.